Investigation of Generation of Electromagnetic Radiation in a Coaxial Vircator with Radially Diverging Deam; International Congress on Energy Fluxes and Radiation Effects, September 21–26, 2014, Tomsk, Russia - Koval T. V. Tamara Vasilievna; Zherlitsyn A. G. Aleksey Grirorievich; Kanaev G. G. Gennady Grigorevich; Shiyan V. P. Vladimir Petrovich; Nguyen Man' Hung (18th International Symposium on High Current Electronics, 2014)
Title screen